Strong electric fields at a prototypical oxide/water interface probed by ab initio molecular dynamics: MgO(001). Issue 31 (21st August 2015) - Laporte, Sara; Finocchi, Fabio; Paulatto, Lorenzo; Blanchard, Marc; Balan, Etienne; Guyot, François; Saitta, Antonino Marco
<x xml:space="preserve">Abstract</x> We report a density-functional theory (DFT)-based study of the interface of bulk water with a prototypical oxide surface, MgO(001), and focus our study on the often-overlooked surface electric field.